2020
DOI: 10.1007/s00467-020-04621-4
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up after neonatal heart disease repair: watch out for chronic kidney disease and hypertension!

Abstract: Background With advances in care, neonates undergoing cardiac repairs are surviving more frequently. Our objectives were to 1) estimate the prevalence of chronic kidney disease (CKD) and hypertension 6 years after neonatal congenital heart surgery and 2) determine if cardiac surgery-associated acute kidney injury (CS-AKI) is associated with these outcomes. Methods Two-center prospective, longitudinal single-visit cohort study including children with congenital heart disease surgery as neonates between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…Similar results were demonstrated by Huynh in neonatal population, that cardiac surgery associated AKI was not associated with chronic kidney disease (GFR <90ml/min/1.73m2) or hypertension. They found however a chronic kidney disease and hypertension prevalence as 17% and 30% respectively in the whole group on follow up of 6 years [10]. Similar results were found in TRIBE-AKI and Zappitelli et al respectively with no correlation of post-operative AKI and chronic kidney disease on follow up [19][20][21][22].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Similar results were demonstrated by Huynh in neonatal population, that cardiac surgery associated AKI was not associated with chronic kidney disease (GFR <90ml/min/1.73m2) or hypertension. They found however a chronic kidney disease and hypertension prevalence as 17% and 30% respectively in the whole group on follow up of 6 years [10]. Similar results were found in TRIBE-AKI and Zappitelli et al respectively with no correlation of post-operative AKI and chronic kidney disease on follow up [19][20][21][22].…”
Section: Discussionsupporting
confidence: 59%
“…Complexity of cardiac surgery was categorized using the risk adjustment for congenital heart surgery-1 (RACHS-1), the consensus-based scoring system commonly used to classify the complexity of cardiac surgeries; with higher scores indicating more complex surgeries [25]. We also recorded the STAT score (The Society of Thoracic Surgeons-European Association for Cardio-Thoracic Surgery), a more objective score for evaluation of our cohort [10,25]. A detailed clinical history, including history of medications taken, duration of hospital stay and need of dialysis was recorded.…”
Section: Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies reported long-term kidney outcomes following PICU-AKI exclusively in subjects who underwent cardiac surgery ( 2 , 4 , 24 , 25 , 29 , 31 ). Unlike the general PICU population, there is conflicting evidence on whether AKI after cardiac surgery is associated with negative long-term kidney outcomes.…”
Section: Hypertension Proteinuria and Chronic Kidney Diseasementioning
confidence: 99%
“…In a cardiac sub-group of 88 heart transplant recipients, advanced CKD (GFR <60 mL/min/1.73 m 2 ) developed in 5% of the population after 1-year follow-up and was more common in those who did not fully recover kidney function and in those with more severe AKI (stage 2 or 3 by KDIGO) ( 2 ). Lastly, in an exclusively neonatal cohort of 58 subjects who underwent cardiac surgery, with a median follow-up of 6 years, AKI was not associated with CKD or hypertension despite a high prevalence overall (17 and 30%, respectively) ( 29 ). Post-operative cyanosis was the only independent predictor of CKD.…”
Section: Hypertension Proteinuria and Chronic Kidney Diseasementioning
confidence: 99%